Overcoming the limitations of low-bandgap Cu2ZnSn(S,Se)4 devices under indoor light conditions: from design to prototype IoT application - Karade, Vijay C.; Lim, Jihoo; Gour, Kuldeep Singh; Jang, Jun Sung; Shin, So Jeong; Kim, Jong H.; Yang, Bum Seung; Choi, Hyuntae; Enkhbat, Temujin; Kim, Jun Ho; Yun, Jae Sung; Jang, Hae Nam; et al. (Journal of Materials Chemistry A, 2022)
With the growing need for cost-effective and sustainable Internet of things (IoT) technologies, kesterite-based solar cells are gaining popularity. We report the fabrication of an efficient CZTSSe absorber layer with improved Voc loss and its possible use in indoor photovoltaic applications. The double cation incorporation (co-doping) approach is employed with Ag and Ge to achieve this. The devices fabricated and tested under standard illumination (1 sun) and low light intensity conditions showed enhanced device performances and lower Voc losses after co-doping. Under indoor light conditions, Voc of 290 mV with white LED (WLED) and 310 mV with fluorescent lamp (FL-4000K) was achieved at the lowest intensity of 400 lux, while a value exceeding 350 mV was obtained at 1200 lux with FL-4000K for the CZTSSe:Ag-Ge device. Voc recoveries of >60% under all intensity conditions and >70% at 1200 lux with both WLED and FL-4000K were achieved. Moreover, the CZTSSe:Ag-Ge device showed efficiencies of 4.95% and 5.85% under WLED and FL-4000K at 1200 lux, respectively. The prototype device also demonstrated successful test results under indoor conditions. These achievements are attributed to the enhanced carrier density, reduced density of defects, and low carrier recombinations.
Keywords: Cell/B.E; Co-doping; Condition; Cost effective; Indoor light; Internet of things technologies; Kesterites; Light conditions; Low bandgap; White LED's